Tote Bag / Ammar Nur Haqim Khairunnas and Muhammad Azhad Huzarein - Khairunnas, Ammar Nur Haqim; Huzarein, Muhammad Azhad (2023)
This section of executive summary gives a general overview of a partnership for the tote bag business while highlighting its salient features, market potential, and tactical approach. The business aims to capitalize on the growing demand for sustainable and eco-friendly alternatives to single-use bags. By forming partnerships with designers, manufacturers, and retailers, the business plans to provide a broad selection of premium tote bags that satisfy the changing requirements of environmentally conscious customers. The business works with designers, but we also accept the designs that are come out by the customers themselves to produce stylish and modern tote bag designs. The target audience for our business will be the students ranging from High School to Universities, which covers the majority of the social media demographic. We guarantee the production of premium tote bags using ethical procedures and sustainable materials through partnerships with manufacturers. We can optimize production costs and achieve economies of scale thanks to these collaborations. In order to increase our reach and increase the potential of a sale, we market our business through Facebook as our marketing platform. We will use a multi-channel marketing and sales strategy that includes the following components to successfully break into the market. We can access diverse sales channels by cooperating with established retailers. We primarily update our content on Facebook, but we also provide our WhatsApp contact information for customers who would rather use a more userfriendly platform. Our tote bag collection is displayed on our Facebook page, which also makes shopping easy. To interact with our target audience on social media, we will also use influencers and social media platforms. Our tote bag partnership company has the potential to benefit from the rising demand for fashionable, environmentally friendly alternatives to single-use bags. We hope to provide a stylish selection of eco-friendly tote bags that satisfy the changing demands of environmentally conscious consumers by fostering collaborations with designers, producers, and retailers. We are positive in the success and profitability of our business venture thanks to a robust market opportunity, a competitive advantage, and a complete marketing and sales strategy.